Design and Development of Smart List: A Mobile App for Creating and Managing Grocery Lists - Katuk et al. (مجلة بغداد للعلوم)
Research in consumer science has proven that grocery shopping is a complex and distressing process. Further, the task of generating the grocery lists for the grocery shopping is always undervalued as the effort and time took to create and manage the grocery lists are unseen and unrecognized. Even though grocery lists represent consumers’ purchase intention, research pertaining the grocery lists does not get much attention from researchers; therefore, limited studies about the topic are found in the literature. Hence, this study aims at bridging the gap by designing and developing a mobile app (application) for creating and managing grocery lists using modern smartphones. Smartphones are pervasive and become a necessity for everyone today. Hence, a smartphone app that can facilitate the process of creating and managing grocery lists for busy and working people is beneficial. The design and development of the app followed the rapid application development methodology. First, the functional requirements were gathered through interviews and content analysis. Then, a prototype named SMART LIST has been developed based on the gathered requirements, and a field study was carried out to evaluate the usability of the prototype. The results of the evaluation suggested that SMART LIST is useful and easy to use. The respondents also satisfied with the functions for managing grocery lists offered by SMART LIST. The study contributes towards an understanding the system requirements and user interface of a mobile app for managing grocery list. It can be a reference model for developers and researchers in the area to develop similar apps or enhancing the capabilities in creating and managing grocery lists.